Migraciones e igualdad/desigualdad - Cohen, Néstor; Gil Araujo, Sandra; Mera, Carolina; Morales, Diego; Novaro, Gabriela; Pacecca, María Inés (Instituto de Investigaciones Gino Germani, Facultad de Ciencias Sociales, UBA, 2021)
Conversaciones realizadas el 25 de septiembre de 2013.